Simulation of Effect a Variable Height of Porous Absorber on Ventilation Solar Chimney Performance - Alshbailat, Suhaib; Nima, Mohammed A. (Al-Nahrain Journal for Engineering Sciences, 2023)
The improvement in solar chimneys' thermal performance and thermal behavior that can be achieved by adding metal foam has been tested in computational work. The flow and heat transfer governing equations for solar chimney models were solved using computational fluid dynamics (CFD). It was solved using the control volume numerical method in ANSYS FLUENT 14.5. It is used to construct a finite volume modeling technique for solving the governing equations and the radiation heat transfer equations. With standard flat absorber plates, the results showed that heat transmission was increased by the inclusion of metal foam (10 PPI), leading to an increase in air velocity at the solar chimney of around 13.3%. The highest average air velocity with 10 PPI drops by 54.4% as the height of the absorber plate changes from 5 cm to 25 cm respectively.